Workshop on Technology for Autonomous Learning for English Teachers and Lecturers in Indonesia - Yansyah Yansyah; Dina Rafidiyah; Hafizhatu Nadia (Perkumpulan Peneliti Ilmu Lingkungan - Green Visioneers, 2018)
Using technology to teach English is not a new thing. Somehow, there are many applications that available for free lately. Very difficult for lecturers and teachers in Banjarmasin, Indonesia, to update the knowledge of the new application and how to use it in their English classes due to limited trainings related to this issue. Therefore, this community service aims to give the insight to lecturers and teachers in Banjarmasin about how to use application in teaching English skills. The workshop conducted in UIN Antasari by three speakers about how to use mentimeter, sli-do, and EdPuzzle for teaching 4 skills of English, namely: speaking, listening, writing and reading. Mostly the lecturers and teachers enjoy the workshop and plan to apply it in their future English classes. They believe that the application introduced can engage the learners and help them to be more autonomous.